Категории «аletheia» и «земля» в философии М. Хайдеггера - Мирошников, О.А. (Культура народов Причерноморья, 2013)
Будучи учеником Э. Гуссерля, М. Хайдеггер в основном разделял взгляды своего учителя. Отход его от феноменологии был связан, помимо прочего, с усвоением им понятий aletheia и земля, которые образовали в его философии категориальную пару. Эта категориальная пара используется им, в частности, при характеристике проблем искусства и познания. Ключевые слова: aletheiа, земля, искусство, художественное творение, познание, истина. Будучи учнем Е. Гуссерля, М. Хайдеггер в основному поділяв погляди свого вчителя. Відхід його від феноменології був пов'язаний, крім іншого, з засвоєнням їм понять aletheia і земля, які утворили в його філософії категоріальну пару. Ця категоріальна пара використовується ним, зокрема, при характеристиці проблем мистецтва і пізнання. Ключові слова: aletheiа, земля, мистецтво, мистецький витвір, пізнання, істина. Heidegger's departure from phenomenology associated, among other things, with the assimilation of his concept of Aletheia. This is the Greek word usually translated as "clearance", but a similar interpretation narrows the thought of Heidegger. His philosophy is more possible to clarify a concept borrowed from the first philosophers at the turn of the 20-ies. Originally aletheia Heidegger acted just as a concept, but not as a category. In the mid 30's. aletheia becomes a category. This was due to the influence of the German thinker's ideas of F. Hölderlin, his compatriot, the poet, who lived in the first half of the XIX century. The image, which corresponds to the Greek word aletheia, in a sense opposed to the poet another way - the land. Both words of Hölderlin - poetic images, but of course, not a clue, and not category. For Heidegger, who has enjoyed a decade and a half as the concept of aletheia, familiarity with the works of the poet was a kind of "breakthrough" (that characterizes the student of Heidegger, Gadamer G.-G. role played in his philosophical works of the poet's biography). Without this effect, most likely, a philosopher would use a slightly different categorical pair (for example, “aletheia - the world”, he came close enough to the second "category "). In one of his most significant works - "The source of artistic creation" - Heidegger for the first time, and rather successfully, using a pair of categorical «aletheia - ground." Through the use of this categorical pairs he does in "The source of artistic creation," a number of significant findings, in particular the conclusion that the truth reveals itself through the human being. In the works of the later period of Heidegger often returned to this categorical pair using it, in particular, to relate the concepts of "truth" and "untruth". The tense dynamic that exists between these categories as well as between the studied concepts led him to the notion of freedom as the assumptions required for the disclosure of the truth. Key words: aletheia, land, art, artistic creation, the knowledge the truth.